Reestructuración comercial administrativa de la empresa H.T.T.P.S. S.A.S. (2018)
This project was developed in the High Performance Petroleum Services S.A.S. Company. The project has as title Restructuration management and commercial in the H.P.P.S. S.A.S. Company, the project was developed because the company was with some problems in the commercial area and management aspects, the oil crisis was around the project started, so is necessary that the strategic planning is focus to the market need. In the project was used tools and concepts viewed in the undergrade, the market investigation and analysis of it, allowed know the necessities that the market has and the opportunities of it.